Hidden Threats - Mala, Faiqotul; Rahman, Fazlul (Proceedings of Annual Conference for Muslim Scholars, 2024)
This article investigates the enduring threat of radicalism among female ex-convicts in Indonesia who, despite seeming disengagement, retain radical ideologies and reject local wisdom. It explores the complexities of their reintegration by examining how their past experiences in radical groups, through the lens of Bourdieu's concept of "habitus," have shaped their persistent beliefs and behaviors. This ingrained mindset resists societal pressures to conform, leading to a continued rejection of local values promoting harmony. The study hypothesizes that this internalized radicalism, despite outward conformity, poses a latent risk of future radicalization and acts of intolerance, acting as a potential trigger for extremism.